Glimpses of glorious Pagan - Ranʻkunʻ Takkasuilʻ. Department of History (Rangoon, Burma Universities Press, 1986)
Description of Buddhist temples in Pagan, Burma.
Keywords: Buddhist temples -- Burma -- Pagan; Pagan (Burma) -- Religion